Era Disrupsi Teknologi Dan Dampaknya Pada Karakter Remaja - Itania Musri; Filmon Berek (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
The future of youth is a very important period and very prone to failure,that is why it is important to have spritual guaidance and how is our role in approaching them to provide understending to youth.why is our role so important to them, because if we don’t set an example and don’t introduce Jesus Christ how will they know.Adolescence is a time when they want to know a lot of things,thoughts that still can’t distinguish which one is good or vice versa make decisions and do everything without thinking.So it’s not often that children experience failure when there is no one to guide and direct what is good and what is not. Failure in relationships even in their character both physically and spiritually. We just still need guidance from our parzents moreover they need us to direct them.